Mengungkap Efektifitas Hukum Ekonomi Syariah di Indonesia - Zulqarnain (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
The development of law often lags behind the dynamics of economic activities, whereas legal certainty is essential to protect the economic and business rights of market participants. This study evaluates the effectiveness of Islamic economic law in Indonesia using Anthony Allott’s theory of legal effectiveness, which emphasizes the preventive, curative, and facilitative functions of law. Employing a qualitative evaluative approach, the analysis draws on statutory laws, fatwas, judicial decisions, and institutional regulations from key authorities such as the Financial Services Authority (OJK), the National Sharia Board (DSN-MUI), and the National Committee for Sharia Economics and Finance (KNEKS), complemented by reputable peer-reviewed academic sources. The findings indicate that Islamic economic law remains partially effective: it has yet to improve public literacy and inclusion, its curative mechanisms are constrained by limited substantive law, and its facilitative role is weakened by regulatory inflexibility. The study contributes to the socio-legal evaluation of Islamic economic law, proposing a more integrated, adaptive, and innovation-oriented framework to enhance the responsiveness and sustainability of Indonesia’s Sharia economic system.